Effects of sling exercise therapy on post-stroke walking impairment: a systematic review and meta-analysis. Issue 1 (29th October 2021) - Long, Junzi; Zhang, Yasu; Liu, Xiaomin; Jin, Xiaoqin
Abstract : Walking impairment is a common consequence of stroke, resulting in long-term disability. Trunk muscle strength has been proven to be associated with post-stroke walking performance. As a type of trunk training, sling exercise therapy (SET) has been widely used to improve the trunk function in stroke patients. The purpose of this systematic review was to investigate the efficacy of SET on post-stroke walking impairment. Seven databases were systematically searched for eligible studies from their inception to 1 August 2021. Review Manager 5.3 software was used for this meta-analysis. The overall quality of included studies was evaluated by the physiotherapy evidence database scale. Twenty-five randomized controlled trials involving 1504 patients were included (23 in China and two in South Korea). In summary, SET more effectively improved the walking ability of post-stroke patients than conventional physical therapy or trunk training. The pooled analysis demonstrated that SET had positive effects on the 10 m maximum walking speed, integrated electromyography value of rectus femoris, biceps femoris and gastrocnemius, functional ambulation category, timed up and go test, and step length. At least in East Asia, our findings support SET to manage the post-stroke walking impairment.